Radiographic evaluation of posttraumatic osteoarthritis of the ankle: the Kellgren–Lawrence scale is reliable and correlates with clinical symptoms. Issue 3 (March 2015) - Holzer, N.; Salvo, D.; Marijnissen, A.C.A.; Vincken, K.L.; Ahmad, A.C.; Serra, E.; Hoffmeyer, P.; Stern, R.; Lübbeke, A.; Assal, M.
Summary: Objective: To assess reliability and construct validity of the Kellgren–Lawrence (K&L) scale in posttraumatic ankle osteoarthritis (OA); additionally evaluate the validity of including tibiotalar tilting in the scale. Method: One-hundred and fifty ankle radiographs (75 patients, unilateral malleolar fractures) evaluated at average of 18 years after surgery. American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot (HF) score and pain (visual analog scale) were recorded. Grading of OA according to K&L criteria and identification of OA features was performed on standardized radiographs by four physicians. Minimal joint space width, sclerosis, and talar tilt angle were quantified by digital measurements. A modified K&L scale including talar tilting is presented. Validity of original and modified scale was evaluated and expressed as ability to (1) Identify those with clinical symptoms of ankle OA; and (2) Distinguish between different degrees of fracture severity. Results: Inter- and intra-observer reliability of OA assessment according to K&L were good (ICC 0.61 and 0.75). Original and modified K&L grades significantly increased with decreasing AOFAS ankle-HF scores and greater pain. A talar-tilt angle >2° compared with ≤2° in grade 3 was associated with significantly higher pain levels (VAS pain 4.2 vs1.4, respectively; mean difference 2.8, 95% CI 0.5–5.1). More severe fracture patterns at time of surgery were more often in patients with the highest K&L grades. Conclusions: The K&L scale is a valid and reliable radiographic grading system for assessment of ankle OA. Inclusion of the talar tilt angle might allow for better differentiation with respect to clinical outcomes.